Diversitas arthropoda tanah pada Ekosistem Kelapa Sawit di Sungai Suci Bengkulu - Sulistyowati, Endang; Malinda, Martina Efri; Afrianti, Widia; Suherman, Dadang; Soetrisno, Edi; Suharyanto, Suharyanto; Badarina, Irma; Akbarillah, Tris (Badan Penerbitan Fakultas Pertanian (BPFP), 2024)
A variety of flavored yogurt has been widely known; however, adding fruit would impact the choice of this product. In this experiment, some fruits, such as Ananas comosus and Cucumis melo had been supplemented in yogurt made from dairy goat milk. This research used a completely randomized design 4 x 4, applying four treatments with four replications. The treatments were FO: yogurt with no addition of fruit; FA: yogurt with 10% fruit Ananas; FC: yogurt with 10% fruit Cucumis; FM: yogurt with mixed addition of 5% fruit Ananas and 5% Cucumis. Data of sensory evaluation and pH were analyzed using Anova. Results showed no significant differences in color, odor and flavour among treatments. However, there was found the highest (P<0.05) score (3.30) on the texture of yogurt with C. melo. On average, this yogurt and mixed fruit yogurt also showed high overall acceptability (2.65). Yet, the Cucumis yogurt had high averages in TPC (2.8×107) and pH (5.72). Cost production, in average, the mixed yogurt showed IDR 105,516 for 2,5 l (IDR 42,206 for 1 l yogurt). It had IDR 5,790 difference from the one with no fruit yogurt. In conclusion, yogurt with A. comosus had an optimal combination of sensory evaluation score, TPC, pH and cost production.